Web-based assessment system for English structured questions - Tan, Xue Feng (2014)
One language that is most widely used in the whole world is the English language. It is the third most common native language, which is no wonder nations all over the world; want to be proficient in English. Having the ability to communicate with other countries open doors to opportunities that could help further prosper the economy and living condition in terms of business, politics, trading, commercial or any other forms of cooperation.